Object-oriented diplomatics: Using archival diplomatics in software application development to support authenticity of digital records. (16th March 2015) - Jansen, Adam
Abstract : Purpose: – This paper aims to present a conceptual methodology, named herein as object-oriented diplomatics, based on a presentation given by the author at the Digital Diplomatics 2014 conference. This methodology centers on building digital records capable of supporting their authenticity over time and when removed from their original systems by extending archival diplomatics theory by leveraging object-oriented programming (OOP) principles. Design/methodology/approach: – This paper presents new method for supporting the presumption of authenticity of digital records through extending archival diplomatics concepts into OOP principles when creating digital records within a record-keeping system. Findings: – This paper is based on a preliminary research being conducted during the design of a government digital archives. This concept was used as a core design element for their digital archives and has thus far shown great promise in articulating and encapsulating those essential data elements that support the presumption of authenticity across a wide diversity of record types. Originality/value: – This paper presents a new approach to support the presumption of authenticity of digital records by utilizing concepts from archival diplomatics leveraged with OOP principles. It is the hope of the author that this paper will initiate a deeper collaboration between archives and records management professionals and software developers in the design and implementation of digital repositories.